Stilistika pada Puisi Sepetak Tanah di Pekarangan dan Sepasang Mata yang Buta Karya Theoresia Rumthe: Stylistics in the Poems 'Sepetak Tanah di Pekarangan' and 'Sepasang Mata yang Buta' by Theoresia Rumthe" - Yulianingsih, Mia; Pratiwi, Wienike Dinar; Suntoko, Suntoko (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Every poet has his own way of writing including the use of a distinctive language style in order to achieve the goal of beauty or aesthetics in his work. The diversity of language styles in poetry is often difficult to understand, especially by novice readers. Difficulty in understanding the language style in poetry can affect the reader's response because it prevents the reader from capturing the meaning contained in it. The purpose of this study was conducted because the researcher intends to examine the use of stylistics in the aspects of sound, lexical elements, and exaggeration. This research uses a qualitative method with an analytical descriptive approach. The subject of this research is a poem entitled Sepetak Tanah di Pekarangan and Sepasang Mata yang Buta by Theoresia Rumthe. The object of this research is the use of stylistics in the form of sound aspects, lexical elements, and maximization. The data analysis technique in this research is carried out through several stages, including data collection, data reduction, data presentation, and conclusion drawing. The results show that the poems entitled Sepetak Tanah di Pekarangan and Sepasang Mata yang Buta by Theoresia Rumthe contain stylistics in the form of sound aspects, including assonance, alliteration, initial rhyme, and final rhymeAspects of meaning, including denotation and connotation. Imagery includes comparison in the form of personification and simile, contradiction in the form of hyperbole and irony.